CoNC oxygen reduction catalyst with controllable particle size and preparation method and application thereof

CN122992090APending Publication Date: 2026-10-27NANHUA UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611036736.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-13
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]现有ZIF衍生CoNC催化剂制备过程中,前驱体颗粒尺寸往往难以精准调控,且常需要引入表面活性剂、模板剂、复杂溶剂体系或高温水热条件

Benefits of technology

(1)本发明不依赖表面活性剂、硬模板或复杂水热设备,仅通过调控钴盐用量并结合室温搅拌和超声处理即可实现Zn/Co双金属ZIF类前驱体粒径调控,制备方法简便、绿色、可重复,适于放大制备。通过调控反应体系中钴盐的浓度,实现了粒径与氧还原性能之间构效关系的建立。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122992090A_ABST
    Figure CN122992090A_ABST
Patent Text Reader

Abstract

The application discloses a CoNC oxygen reduction catalyst with adjustable particle size and a preparation method and application thereof. A zinc salt and a cobalt salt are dissolved in an alcohol solvent, and 2-methyl imidazole is dissolved in an alcohol solvent; the two are mixed, stirred at room temperature, subjected to segmented ultrasonic treatment, stirred again and subjected to ultrasonic treatment again to obtain a Zn / Co bimetallic ZIF precursor; the Zn / Co metal ZIF precursor is subjected to centrifugation, washing and drying, and then subjected to high-temperature pyrolysis under an inert gas atmosphere to obtain a cobalt-nitrogen-doped carbon oxygen reduction catalyst with controllable particle size. The application adjusts the amount of the cobalt salt and adopts segmented stirring and segmented ultrasonic treatment, and makes the cobalt-nitrogen-doped carbon-based catalytic system rich in Co-Nx active sites and microporous structures. The catalyst prepared under the conditions of the application has a half-wave potential of 0.86 V in an alkaline oxygen reduction reaction, and the structure-activity relationship between the particle size and the oxygen reduction performance is established.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst technology, specifically to a CoNC oxygen reduction catalyst with tunable particle size, its preparation method, and its application. Background Technology

[0002] As the global energy structure shifts towards cleaner and lower-carbon energy, fuel cells, with their high energy conversion efficiency and low emissions, have become a crucial technology for replacing traditional fossil fuels. However, the commercialization of fuel cells still faces numerous challenges, with the sluggish kinetics of the oxygen reduction reaction (ORR) at the cathode being a key bottleneck. ORR typically involves multi-electron transfer processes with complex reaction pathways, traditionally relying on platinum-based noble metal catalysts to achieve efficient four-electron reduction pathways. However, the scarcity, high cost, and insufficient long-term stability of platinum resources limit its large-scale application. Therefore, developing high-performance, low-cost non-noble metal ORR catalysts has become a current research hotspot.

[0003] Among numerous non-noble metal catalysts, transition metal-nitrogen-carbon (MNC) composites, especially cobalt-based carbon-nitrogen (CoNC) materials, have attracted considerable attention due to their excellent electrical conductivity, abundant active sites, and high intrinsic ORR activity. ZIF-67, as a typical cobalt-based zeolite imidazolium ester framework material, possesses a high specific surface area, tunable pore structure, and abundant nitrogen coordination sites, making it an ideal precursor for preparing CoNC catalysts. Studies have shown that catalyst particle size significantly affects its ORR performance; smaller sizes generally facilitate the exposure of more active sites and shortens the mass transfer pathway. However, how to simply and controllably adjust the particle size of ZIF-67-derived catalysts and systematically elucidate its relationship with ORR performance remains a pressing scientific problem.

[0004] In the preparation of existing ZIF-derived CoNC catalysts, the precursor particle size is often difficult to control precisely, and it often requires the introduction of surfactants, template agents, complex solvent systems, or high-temperature hydrothermal conditions. While bimetallic systems offer excellent performance, their synthetic routes are relatively complex. Existing particle size control strategies, such as introducing surfactants, changing solvents, or employing hydrothermal synthesis, are often cumbersome, energy-intensive, and unsuitable for large-scale production. The paper "Fabricating Co–N–C catalysts based on ZIF-67 for oxygen reduction reaction in alkaline electrolyte" (Jia-PingXuan, Journal of Solid State Chemistry, Volume 294, February 2021, 121788) synthesized approximately 300 nm rhombic dodecahedral ZIF-67 using a 1:6 molar ratio of cobalt nitrate to 2-methylimidazole. This article controlled the morphology and particle size of ZIF-67 by adjusting the amount of raw materials, but proposed that the particle size of the rhombic dodecahedral ZIF-67 decreased with increasing 2-methylimidazole content. However, whether catalyst particle size follows this rule depends on the preparation method, and whether smaller particle size necessarily leads to better catalytic performance requires further investigation. Therefore, achieving a balance between active site exposure, pore structure inheritance, electron transport, and mass transfer efficiency is a key technical problem that urgently needs to be solved in this field. Summary of the Invention

[0005] To address the aforementioned limitations of existing technologies, the present invention aims to provide a CoNC oxygen reduction catalyst with tunable particle size, its preparation method, and its applications. This invention uses zinc salt, cobalt salt, and 2-methylimidazole as main raw materials. By adjusting the amount of cobalt salt, the supersaturation and nucleation-growth kinetics of the reaction system are altered. Furthermore, segmented stirring and segmented ultrasonic treatment are used to enhance mass transfer and uniform nucleation, resulting in Zn / Co bimetallic ZIF-type precursors with different particle sizes. These precursors are then pyrolyzed under an inert atmosphere to transform into a cobalt-nitrogen-doped carbon-oxygen reduction catalyst with controllable particle size, microporous structure, and Co-Nx active centers.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: In a first aspect, the present invention provides a method for preparing a CoNC oxygen reduction catalyst with tunable particle size, comprising the following steps: Zinc and cobalt salts were dissolved in alcohol solvents to obtain metal salt solutions, and 2-methylimidazole was dissolved in methanol to obtain imidazole solutions. The imidazole solutions were added dropwise to the metal salt solutions, and the mixture was stirred at room temperature to obtain a homogeneous solution. The homogeneous solution was subjected to a first ultrasonic treatment, stirred again, and then subjected to a second ultrasonic treatment. The solution was centrifuged, washed, and dried. The dried product was calcined under an inert atmosphere to obtain a black solid, which is the CoNC oxygen reduction catalyst.

[0007] Preferably, the molar ratio of the zinc salt, cobalt salt, and 2-methylimidazole is 4.2:0.1~0.8:23.6; the volume ratio of the metal salt solution to the imidazole solution is 1:1; and the alcohol solvent is methanol.

[0008] Preferably, the molar ratio of the zinc salt, cobalt salt and 2-methylimidazole is 4.2:0.4:23.6.

[0009] Preferably, the stirring time at room temperature is 48 hours.

[0010] Preferably, the first ultrasound treatment is: 3 hours of ultrasound, 1 hour each time, with a 10-minute interval between each time.

[0011] Preferably, the re-stirring time is 12 hours.

[0012] Preferably, the second ultrasound treatment lasts for 3 hours, with each session lasting 1 hour and each session lasting 10 minutes.

[0013] Preferably, the calcination temperature is 900°C and the time is 3 hours.

[0014] In a second aspect, the present invention provides a CoNC oxygen reduction catalyst with tunable particle size obtained by the above preparation method, wherein the CoNC oxygen reduction catalyst is prepared by a molar ratio of zinc salt, cobalt salt and 2-methylimidazole of 4.2:0.4:23.6; and the average particle size of the CoNC oxygen reduction catalyst is 480~490 nm.

[0015] A third aspect of the present invention provides the application of a CoNC oxygen reduction catalyst with tunable particle size in the catalytic cathode oxygen reduction reaction.

[0016] Preferably, the half-wave potential of the cathode oxygen reduction reaction and the particle size of the CoNC oxygen reduction catalyst both increase first and then decrease with the cobalt salt concentration; when the average particle size of the CoNC oxygen reduction catalyst is 480~490nm, the half-wave potential of the CoNC oxygen reduction catalyst in 0.1 mol / L KOH electrolyte is above 0.86 V, and the half-wave potential is referenced with RHE.

[0017] The beneficial effects of this invention are: (1) This invention does not rely on surfactants, hard templates or complex hydrothermal equipment. The particle size of Zn / Co bimetallic ZIF precursors can be controlled simply by adjusting the amount of cobalt salt and combining room temperature stirring and ultrasonic treatment. The preparation method is simple, green and reproducible, and suitable for scale-up preparation. By controlling the concentration of cobalt salt in the reaction system, the structure-activity relationship between particle size and oxygen reduction performance is established.

[0018] (2) The present invention adopts segmented stirring-segmented ultrasonic treatment. The microjets and shock waves generated by ultrasonic cavitation can enhance mass transfer, eliminate local concentration gradients, promote uniform nucleation and inhibit soft agglomeration, which is beneficial to obtaining Zn / Co bimetallic ZIF precursors with uniform particle size distribution and good structural inheritance.

[0019] (3) The catalyst prepared by this invention has a predominantly microporous pore structure and a high specific surface area, which is beneficial for exposing Co-Nx active centers and improving the transport efficiency of oxygen, OH⁻ and reaction intermediates, thereby increasing the ORR half-wave potential and limiting current density. Under the preferred cobalt salt dosage, the obtained catalyst can achieve a half-wave potential of 0.86 V (vs. RHE) and a limiting current density of 4.72 mA / cm². 2 The electron transfer number is close to 4, indicating that it has good selectivity and application potential in the four-electron oxygen reduction reaction pathway. Attached Figure Description

[0020] Figure 1 : A schematic diagram of the preparation process of the cobalt nitrogen-doped carbon-oxygen reduction catalyst with controllable particle size of the present invention; Figure 2 XRD pattern of CoNC-0.4; Figure 3 (a) Particle size distribution of CoNC-0.1; (b) Particle size distribution of CoNC-0.2; (c) Particle size distribution of CoNC-0.4; (d) Particle size distribution of CoNC-0.6; (e) Particle size distribution of CoNC-0.8; (f) Average particle size distribution of CoNC prepared at different concentrations. Figure 4SEM images of CoNC catalysts prepared under different cobalt salt dosages: (a) SEM image of CoNC-0.1, scale bar 500 nm; (b) SEM image of CoNC-0.1, scale bar 1 μm; (c) SEM image of CoNC-0.2, scale bar 500 nm; (d) SEM image of CoNC-0.2, scale bar 1 μm; (e) SEM image of CoNC-0.4, scale bar 500 nm; (f) SEM image of CoNC-0.4, scale bar 1 μm; (g) SEM image of CoNC-0.6, scale bar 500 nm; (h) SEM image of CoNC-0.6, scale bar 1 μm; (i) SEM image of CoNC-0.8, scale bar 500 nm; (j) SEM image of CoNC-0.8, scale bar 1 μm. Figure 5 (a) Nitrogen adsorption-desorption curve of CoNC-0.4; (b) DFT pore size distribution of CoNC-0.4; Figure 6 LSV curves of oxygen reduction reaction of CoNC catalysts prepared under different cobalt salt dosage conditions; Figure 7 Cdl curves of CoNC prepared at different concentrations; Figure 8 LSV curves of the oxygen reduction reaction of the CoNC catalysts prepared in Example 1 and Comparative Examples 2-3; Figure 9 (a) XPS of the CoNC catalyst prepared in Example 1; (b) C 1s high-resolution spectrum; (c) N 1s high-resolution spectrum; (d) Zn 2p high-resolution spectrum; (e) Co 2p high-resolution spectrum; Figure 10 The number of electrons transferred and the H2O2 yield of the CoNC catalysts prepared in Example 1 and Comparative Example 1 during the catalytic oxygen reduction reaction. Detailed Implementation

[0021] It should be noted that the following detailed descriptions are illustrative and intended to provide further explanation of this application. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains.

[0022] As described in the background section, the precursor particle size is often difficult to precisely control in the preparation of existing ZIF-derived CoNC catalysts, and often requires the introduction of surfactants, template agents, complex solvent systems, or high-temperature hydrothermal conditions. While bimetallic systems offer excellent performance, their synthetic routes are relatively complex. Existing particle size control strategies, such as introducing surfactants, changing solvents, or employing hydrothermal synthesis, are often cumbersome, energy-intensive, and unsuitable for large-scale production.

[0023] Based on this, the purpose of this invention is to provide a CoNC oxygen reduction catalyst with tunable particle size, its preparation method, and its applications. This invention proposes a simple room-temperature stirring-segmented ultrasonic synthesis strategy, which effectively controls the particle size of the Zn / Co bimetallic ZIF precursor simply by changing the cobalt salt concentration, thereby controlling the particle size of the CoNC catalyst after pyrolysis. Furthermore, the introduction of ultrasound into the solution reaction system aims to enhance mass transfer, promote multiphase mixing, and accelerate the reaction process using ultrasonic cavitation effects; in particular, ultrasound has significant advantages in the fine control of product size. The local extreme high temperature and pressure generated by ultrasonic cavitation, along with the resulting microjets and shock waves, can induce rapid and uniform nucleation of reactants, making the nucleation process highly concentrated in time, thus laying the foundation for obtaining small size and narrow distribution. Simultaneously, the mechanical action generated by cavitation can effectively disperse existing particles or soft aggregates, inhibiting their further growth, and eliminate local concentration gradients through intense micromixing, avoiding abnormal growth. Therefore, introducing ultrasound into the solution reaction not only improves reaction efficiency but is also an important means to achieve controllable product size, uniform distribution, and tunable morphology. This method requires no complex reagents or equipment, is environmentally friendly, and has high reproducibility. Therefore, this invention uses a Zn / Co bimetallic ZIF-type precursor to systematically study the effect of cobalt salt concentration on the particle size of the precursor and the final CoNC catalyst, establishes the structure-activity relationship between particle size and ORR performance, and explores its application potential in fuel cell cathodes. This work will provide new ideas and experimental foundations for the efficient and controllable preparation of non-precious metal ORR catalysts.

[0024] To enable those skilled in the art to better understand the technical solution of this application, the technical solution of this application will be described in detail below with reference to specific embodiments.

[0025] The test materials used in the embodiments of this invention are all conventional test materials in the art and can be purchased through commercial channels.

[0026] Example 1: Preparation of CoNC oxygen reduction catalyst (1) such as Figure 1As shown, 4.2 mmol of zinc nitrate and 0.4 mmol of cobalt nitrate were weighed and added to 250 mL of methanol, and stirred until completely dissolved to obtain solution A. 23.6 mmol of 2-methylimidazole was weighed and added to 250 mL of methanol, and stirred until completely dissolved to obtain solution B. Solution B was added to solution A through a separatory funnel to form a homogeneous solution.

[0027] (2) Stir the homogeneous solution at room temperature for 48 h; then perform the first ultrasonic treatment for a total of 3 h with each ultrasonic treatment lasting 1 h and each treatment lasting 10 min (without stirring during ultrasonic treatment), with an ultrasonic frequency of 40 kHz and a power of 246 W; then continue stirring for 12 h, and perform the second ultrasonic treatment for a total of 3 h with each ultrasonic treatment lasting 1 h and each treatment lasting 10 min (without stirring during ultrasonic treatment), with an ultrasonic frequency of 40 kHz and a power of 246 W.

[0028] (3) After the reaction was completed, the reaction system was centrifuged and the precipitate was collected. The precipitate was washed three times with methanol and ethanol, respectively, with a centrifugation speed of 10,000 r / min, a centrifugation time of 7 min, and a washing time of 5 min. The washed precipitate was placed in a vacuum drying oven at 60℃ and dried for 12 h to obtain the Zn / Co metal ZIF precursor.

[0029] (4) Place the Zn / Co bimetallic ZIF precursor into a ceramic boat, then into a tube furnace, and heat it to 900°C in an Ar atmosphere for 3 hours (heating rate 5°C / min) to obtain the final black solid, which is the CoNC oxygen reduction catalyst, denoted as CoNC-0.4 (or CoNC-0.4 secondary ultrasound). Figure 2 The synthesized sample was identified by X-ray diffraction (XRD). After pyrolysis, the sample showed broad diffraction peaks related to carbon materials at approximately 26° and 44°, indicating that the Zn / Co bimetallic ZIF precursor was transformed into a carbon-based material after high-temperature pyrolysis. Figure 9 (a) X-ray photoelectron spectroscopy (XPS) analysis, full spectrum scan: This is the most direct evidence. The characteristic peaks of elements such as Zn, Co, N, C, and O should appear clearly in the full XPS spectrum simultaneously. The simultaneous presence of Zn and Co peaks is the primary indicator of bimetallic formation. Figure 9 (b) C 1s high-resolution spectrum: Two characteristic peaks appear simultaneously at ~284.8 eV (CC) and ~286.0 eV (CN), which constitute the N1s high-resolution spectrum for determining the integrity of the 2-methylimidazolium ligand skeleton. Figure 9(c): This demonstrates the coordination between the metal and the ligand. After peak separation, a peak corresponding to the MN (Metal-N) or MNM bond (approximately 399-400 eV) should be observed. The appearance of this peak directly proves that the Zn and / or Co ions form a coordinate bond with the nitrogen atom in the 2-methylimidazolium. Figure 9 (d) Zn 2p high-resolution spectrum: Focus on Zn 2p 3 / 2 and Zn 2p 1 / 2 Two spin orbital peaks. Typical Zn. 2+ The peak position is approximately 1021-1022 eV (Zn 2p 3 / 2 ) and 1044-1045 eV (Zn 2p 1 / 2 If these two peaks appear, it indicates that Zn exists in the framework in a +2 valence state. Co 2p high-resolution spectrum ( Figure 9 (e): The Co 2p spectrum is very distinctive, with the main peak typically appearing at ~781 eV (Co 2p). 3 / 2 Its satellite peak is approximately ~786 eV. This companion peak structure is Co 2+ The presence of these characteristics strongly proves that Co has been successfully coordinated. This indicates that the CoNC material prepared by this invention is a composite ZIF, with Co-N... x It is the main active site.

[0030] Comparative Example 1 The difference from Example 1 is that the concentrations of cobalt nitrate were 0.1, 0.2, 0.6, and 0.8 mmol, respectively. The final CoNC oxygen reduction catalysts were designated as CoNC-0.1, CoNC-0.2, CoNC-0.6, and CoNC-0.8, respectively.

[0031] Example 2: Effect of catalyst morphology and particle size control Statistical analysis was performed on the SEM images of CoNC synthesized at different precursor concentrations, and histograms of particle size distribution and trend graphs of average particle size variation with concentration were plotted for each sample. Figures 3-4 As shown, the overall trend is intuitively presented from the average particle size plot.

[0032] Figure 3The average particle size plot clearly reveals the non-monotonic dependence of CoNC catalyst particle size on precursor concentration. Analysis using the Nano Measurer program yielded average particle sizes of 124.872 nm for CoNC-0.1, 304.371 nm for CoNC-0.2, 485.277 nm for CoNC-0.4, 276.109 nm for CoNC-0.6, and 259.668 nm for CoNC-0.8 at different concentrations. Within a certain concentration range, the average particle size gradually increases with increasing concentration, reaching a maximum at the addition of 0.4 mmol of cobalt nitrate. Subsequently, further increases in precursor concentration not only failed to increase particle size further but also led to a significant decrease in average particle size. This volcano-like variation curve, characterized by an initial increase followed by a decrease, not only statistically confirms the morphological evolution observed in SEM but also provides crucial geometric parameters for subsequent electrochemical performance analysis. Comparing the average particle size variation curve with the ORR half-wave potential and double-layer capacitance variation curves reveals a high degree of synchronicity among the three, all reaching their peak values ​​at the optimal particle size corresponding to moderate concentrations. This correlation between particle size and electrocatalytic performance further indicates that smaller average particle size is not necessarily more advantageous; rather, there exists an optimal size window that allows the derived carbon-based catalyst to achieve the best balance between active site exposure, mass transfer efficiency, and carbon framework stability. Therefore, the "increase-then-decrease" pattern visually presented by the average particle size plot provides direct and strong statistical evidence for the feasibility of optimizing oxygen reduction performance through concentration-controlled particle size.

[0033] like Figure 4 As shown in the scanning electron microscope (SEM) images, the particle size of the CoNC catalyst exhibits a typical non-monotonic response to the precursor solution concentration. Within a certain concentration range, as the cobalt nitrate concentration gradually increases, the average particle size of the CoNC catalyst does not increase linearly, but first undergoes a significant growth phase, reaching its maximum value near a certain critical concentration. Subsequently, if the reactant concentration continues to increase, the particle size decreases sharply, exhibiting an overall morphological evolution pattern of "increasing first and then decreasing." This "large particle engulfing small particle" ripening effect further increases the average particle size of the material, causing the particle size to increase with increasing concentration.

[0034] Example 3: Hole Structure Test Depend on Figure 5The nitrogen adsorption-desorption isotherms and the pore size distribution diagram analyzed by density functional theory (DFT) show that the CoNC material prepared in Example 1 exhibits typical micropore-dominated characteristics and a high specific surface area. From the morphology of the adsorption-desorption isotherms, the sample shows a steep increase in nitrogen adsorption in the low-pressure region (P / P0 < 0.1), which is typical of type I isotherms and direct evidence of capillary filling in the microporous material. The DFT pore size distribution further shows that the pore size is mainly concentrated in the microporous region below 2 nm, and the distribution is narrow, with no obvious mesoporous peaks. This well-developed microporous structure originates from the in-situ inheritance and activation of the regularly arranged imidazole ligand cavities in the ZIF-67 precursor framework during high-temperature carbonization. During pyrolysis, the vacancies left after the volatilization or reduction of zinc or cobalt metal centers, and the pores etched by the escape of small molecule gases generated from the decomposition of organic ligands, collectively construct a high-density microporous network, thus endowing the material with a high Brunauer-Emmett-Teller (BET) specific surface area (861.5 m²). 2 / g).

[0035] It should be noted that this high micropore content and high specific surface area are not isolated structural characteristics, but are intrinsically related to the aforementioned trend in particle size variation. When the precursor concentration is moderate and the particle size is within the optimal range, the ZIF-67 polyhedral particles maintain the complete microporous framework inheritance efficiency, and the mass transfer distance deep within the pores is shortened due to the moderate reduction in particle size. This allows nitrogen molecules to fully explore more of the micropore inner surface during testing, thus exhibiting the highest specific surface area and micropore volume. If the particles are too large, some internal pores cannot be fully detected due to limited mass transfer; if the particles are too small due to explosive nucleation, although the theoretical specific surface area is very high, particle agglomeration and pore collapse during pyrolysis will cause a certain loss of specific surface area. Therefore, the high specific surface area and micropore-dominated characteristics revealed by nitrogen adsorption-desorption and DFT pore structure analysis not only directly prove that CoNC materials possess abundant potential active site carriers and mass transfer channels, but also provide key pore structure explanations for the aforementioned electrochemical laws that the ORR half-wave potential and double-layer capacitance increase first and then decrease with concentration.

[0036] Experimental Example 1 Take 10 mg of the catalyst prepared in Example 1 and Comparative Example 1, add 635 μL of deionized water, 1270 μL of anhydrous ethanol, and 100 μL of Nafion solution, and then sonicate for 10 min to form a homogeneous mixture. Drop 5 μL of the mixture onto a 4 mm diameter disk electrode, and then dry at room temperature at 300 rpm. The catalyst loading is 0.198 mg / cm². 2 .

[0037] All electrochemical tests were performed on a Corrtest CS2350M workstation. The electrolyte was 0.1 MkOH solution, and a three-electrode system was used. The reference electrode was an Hg / HgO electrode, the counter electrode was a platinum sheet, and the working electrode was a catalyst-coated rotating disk electrode / rotating ring disk electrode (RDE / rotating ring disk electrode (RRDE)).

[0038] The LSV scan rate was 10 mV / s, the rotation speed of the rotating ring-disc electrode (RRDE) was 1600 rpm, and the electrolyte was 0.1 M KOH. The LSV curve was first obtained by saturating with O2, then by saturating with Ar gas. The standard LSV curve was obtained by subtracting the current value of the LSV curve obtained with Ar gas from the current value of the LSV curve obtained with O2. E(vs.RHE) = E(Hg / HgO, 1M KOH)+0.098+0.059 pH; The test temperature was room temperature (25℃). The change in the oxygen reduction reaction (ORR) half-wave potential with precursor solution concentration, measured by linear sweep voltammetry (LSV), is shown below. Figures 6-7 As shown.

[0039] The size variation trend of the CoNC material observed by SEM shows a high degree of consistency with the trend of initial increase followed by decrease, exhibiting a non-monotonic pattern. This correlation reveals a profound intrinsic link between material morphology and electrocatalytic performance. Figure 6 As shown, at lower synthesis concentrations, ZIF-67 particles are larger, resulting in correspondingly larger pyrolysis-derived catalyst particles. Although larger particles typically imply lower specific surface area, their more complete carbon framework structure after pyrolysis, due to sufficient growth and higher crystallinity, may lead to more optimized nitrogen doping and coordination environments for cobalt active centers. However, excessively large particles often result in active sites being primarily distributed on the particle surface, while numerous internal sites are embedded, hindering their effective participation in the catalytic reaction. Furthermore, insufficient specific surface area limits mass transfer efficiency, resulting in a relatively low half-wave potential. As the concentration gradually increases to near the critical value, the particle size increases to an optimal range, where the pyrolysis products achieve a better balance between specific surface area, active site exposure, and carbon framework conductivity, maximizing the ORR half-wave potential. Further increases in concentration lead to a sharp decrease in CoNC particle size. While catalysts derived from smaller precursors often have higher specific surface areas, they also exhibit richer defect structures and higher carbon framework disorder. Additionally, excessively small particles are prone to agglomeration and fusion during pyrolysis, which is detrimental to the sufficient exposure and stability of active sites. Therefore, the half-wave potential decreases after the particle size exceeds the optimal value.

[0040] pass Figure 7 Linear scanning voltammetry was used to measure the charge-discharge curves of the electric double layer in the non-Radida potential range. The electric double layer capacitance (Cdl) obtained by linear fitting showed a non-monotonic law that was highly consistent with the change in particle size during SEM analysis as the precursor solution concentration increased; that is, it first increased and then decreased, reaching a maximum value at a moderate concentration (i.e., with the addition of 0.4 mmol of cobalt nitrate). Since the value of Cdl is proportional to the electrochemical active area (ECSA) of the electrode in similar electrode material systems, and ECSA is directly governed by the specific surface area and surface accessibility of the catalyst, this phenomenon essentially reflects the progressive regulation of the microporous structure and active surface exposure of the CoNC-derived carbon material by the precursor solution concentration.

[0041] The CoNC catalysts prepared in Example 1 and Comparative Example 1 were subjected to ring-disk electrode polarization tests at 1600 rpm. The measured ring current and disk current were calculated using the following formula: (1); (2); Where N=0.25 is the collection efficiency, I D For disk current, I R Let n be the ring current and n be the number of transferred electrons (corresponding to the n electron transfer paths).

[0042] Different reaction pathways result in completely different catalytic products. When the reaction is based on a two-electron pathway, the reduction product is excess H₂O₂. However, when the reaction pathway is a four-electron pathway, the product is water. To clarify the reaction pathway of the catalyst, the number of electrons transferred and the H₂O₂ yield of the CoNC catalyst in the catalytic oxygen reduction reaction were obtained. Figure 10 As can be seen, the CoNC catalyst exhibits excellent four-electron selectivity.

[0043] Comparative Example 2: No ultrasonic treatment The difference from Example 1 is that the ultrasonic treatment in step (2) is not performed. The final CoNC oxygen reduction catalyst is denoted as CoNC-0.4 without ultrasonic treatment.

[0044] Comparative Example 3: One ultrasound The difference from Example 1 is that step (2) only involves the first ultrasonic treatment. The final CoNC oxygen reduction catalyst is denoted as CoNC-0.4, which is sonicated once.

[0045] Experimental Example 2 The catalysts prepared in Example 1 and Comparative Examples 2-3 were tested according to the method in Experimental Example 1. The results are as follows: Figure 8 As shown.

[0046] like Figure 8As shown, the oxygen reduction half-wave potential without ultrasonic treatment was 0.81 V, which increased to 0.82 V after one ultrasonic treatment, and significantly increased to 0.86 V after a second ultrasonic treatment. This increasing trend indicates that ultrasonication promotes the uniform dispersion of the catalyst and the exposure of active sites, thereby increasing the electrochemical active area and improving reaction mass transfer. Ultimately, this leads to a significant enhancement of the oxygen reduction reaction kinetics, resulting in a gradual increase in the half-wave potential.

[0047] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.

Claims

1. A method for preparing a CoNC oxygen reduction catalyst with tunable particle size, characterized in that, Includes the following steps: Zinc and cobalt salts were dissolved in alcohol solvents to obtain metal salt solutions, and 2-methylimidazole was dissolved in methanol to obtain imidazole solutions. The imidazole solutions were added dropwise to the metal salt solutions, and the mixture was stirred at room temperature to obtain a homogeneous solution. The homogeneous solution was subjected to a first ultrasonic treatment, stirred again, and then subjected to a second ultrasonic treatment. The solution was centrifuged, washed, and dried. The dried product was calcined under an inert atmosphere to obtain a black solid, which is the CoNC oxygen reduction catalyst.

2. The preparation method according to claim 1, characterized in that, The molar ratio of the zinc salt, cobalt salt, and 2-methylimidazole is 4.2:0.1~0.8:23.6; the volume ratio of the metal salt solution to the imidazole solution is 1:1; and the alcohol solvent is methanol.

3. The preparation method according to claim 2, characterized in that, The molar ratio of the zinc salt, cobalt salt, and 2-methylimidazole is 4.2:0.4:23.

6.

4. The preparation method according to claim 1, characterized in that, The first ultrasound treatment consisted of 3 hours of ultrasound, with each session lasting 1 hour and each session spaced 10 minutes apart.

5. The preparation method according to claim 1, characterized in that, The stirring time at room temperature is 48 hours; the second stirring time is 12 hours.

6. The preparation method according to claim 1, characterized in that, The second ultrasound treatment lasted for 3 hours, with each session lasting 1 hour and each session lasting 10 minutes.

7. The preparation method according to claim 1, characterized in that, The calcination temperature was 900℃ and the time was 3 hours.

8. The CoNC oxygen reduction catalyst with tunable particle size obtained by the preparation method according to any one of claims 1 to 7, characterized in that, The CoNC oxygen reduction catalyst was prepared by mixing zinc salt, cobalt salt and 2-methylimidazole in a molar ratio of 4.2:0.4:23.6; the average particle size of the CoNC oxygen reduction catalyst was 480~490 nm.

9. The application of the CoNC oxygen reduction catalyst with adjustable particle size as described in claim 8 in the catalytic cathode oxygen reduction reaction.

10. The application according to claim 9, characterized in that, When the average particle size of the CoNC oxygen reduction catalyst is 480~490nm, the half-wave potential of the CoNC oxygen reduction catalyst in 0.1 mol / L KOH electrolyte is above 0.86 V, and the half-wave potential is referenced with RHE.